Assessment of radioactivity of ²²⁶Ra, ²³²Th and ⁴⁰K in soil and plants for estimation of transfer factors and effective dose around Mkuju River Project, Tanzania - Banzi, F.; Msaki, P.; Mohammed, N. (Розробка родовищ, 2017)
Purpose. To establish pre-mining indicators to assess radiological impact as a result of release of radionuclides to environment during uranium mining at Mkuju River Project radioactivity of ²²⁶Ra, ²³²Th and ⁴⁰K in soil, plants, fruits and cereals. Findings. The results revealed a strong positive correlation (r) of 0.947 and 0.950 for ²²⁶Ra and ²³²Th, respectively, between values determined in soils and plants. Implicit in these finding is that the distribution of radionuclides in soils is directly proportional to the corresponding radionuclides in plants.